2018
DOI: 10.1007/s11136-018-1964-7
|View full text |Cite
|
Sign up to set email alerts
|

Subjectively different but objectively the same? Three profiles of QoL in people with severe mental health problems

Abstract: PurposeQuality of life (QoL) is a broad outcome that is often used to assess the impact of treatment and care interventions in mental health services. QoL, however, is known to be influenced by individual values and preferences. To investigate this heterogeneity on the individual level, this study aimed to distinguish classes with distinct QoL profiles in a broad group of people with severe mental health problems and to identify the QoL domains that are most strongly related to the classes.MethodsQoL data of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…A two-factor structure of the MANSA may provide a hypothesis for explaining the frequently replicated finding that patients with schizophrenia report high levels of SQoL despite their often disadvantaged living conditions, a phenomenon known as the "disability paradox" [27]. Indeed, previous studies have consistently reported weak associations between objective indicators and SQoL [28,29]. The present analysis specifies those findings further.…”
Section: Discussionsupporting
confidence: 56%
“…A two-factor structure of the MANSA may provide a hypothesis for explaining the frequently replicated finding that patients with schizophrenia report high levels of SQoL despite their often disadvantaged living conditions, a phenomenon known as the "disability paradox" [27]. Indeed, previous studies have consistently reported weak associations between objective indicators and SQoL [28,29]. The present analysis specifies those findings further.…”
Section: Discussionsupporting
confidence: 56%
“…The first core version targets people with psychiatric problems and people treated in forensic psychiatry and includes 3 domains of the Lancashire Quality of Life Profile (LQoLP) [ 11 ]: safety, living situation, and finances. A recent study indicates that these 3 LQoLP domains are universal [ 12 ]. The LQoLP uses a 7-point Likert scale, ranging from 1 (cannot be worse) to 7 (cannot be better).…”
Section: Methodsmentioning
confidence: 99%
“…Second, in mental health, quality of life is understood as an inherently subjective concept that is shaped by individuals’ values and preferences [ 9 - 11 ]. Research underlines this notion [ 12 - 14 ], which calls for further personalization of quality of life measurements. Third, quality of life assessment instruments may promote patient empowerment by providing patients with insight into their quality of life scores, which is an important prerequisite for shared decision making [ 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first core version targets people with psychiatric problems and people treated in forensic psychiatry and includes 3 domains of the Lancashire Quality of Life Profile (LQoLP) [53]: safety , living situation , and finances . A recent study indicates that these 3 LQoLP domains are universal for people with psychiatric problems and people treated in forensic psychiatry [54]. The LQoLP uses a 7-point Likert scale, ranging from cannot be worse (1) to cannot be better (7).…”
Section: Methodsmentioning
confidence: 99%